Strategi Guru PAI dalam Mengelola Beban Administratif untuk Efektivitas Pengajaran di Sekolah Dasar - Widyaningsih, Erna; Subando, Joko (Lembaga Yasin AlSys, 2025)
This study aims to explore the strategies employed by Islamic Religious Education (PAI) teachers in managing administrative workloads to maintain teaching effectiveness in elementary schools within the Karangpandan District. Using a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and documentation involving PAI teachers selected purposively based on their active participation in school activities. The findings reveal that teachers face various administrative burdens, including lesson plan development, e-report card input, activity reporting, and Dapodik data entry, all of which diminish their focus on instructional activities. To address this, teachers adopt time management strategies, collaborate through Teacher Working Group (KKG) forums, and utilize digital technology. Support from school principals and training in Information and Communication Technology (ICT)-based administration have also proven effective in alleviating teacher workload. Conducted from February to April 2025, this study contributes to the formulation of education policies that support teachers, particularly in simplifying administrative tasks and enhancing professional support. Furthermore, it recommends the development of teacher competencies focused on integrating technology into learning documentation and reporting processes.